Microfacies analysis of the Late Maastrichtian- Danian Phosphatic Succession in the H3-Trebeel district, Western Desert of Iraq - Mousa, Anwar K.; Al-Dulaimi, Salam I.; Mohammed, Ibrahim Q. (Iraqi Journal of Science, 2021)
The Late Maastrichtian–Danian phosphatic succession prevails as a deposit to the west of Rutbah region, Western Iraq. This is manifested through the lithostratigraphic sections of boreholes (K.H5\6 and K.H 5\8) drilled previously in the area. The succession is mainly composed of phosphate, shale, porcelanite, oyster and foraminiferal carbonate lithofacies belonging to Digma and Akashat formations. Three facies associations are distinguished during the study: the phosclast planktonic (FA1) that dominates the outer ramp, the phosclast foraminiferal (FA2) that dominates the mid ramp, and the quartz dolomitic phosclast (FA3) present in the inner ramp. These facies’ associations are differentiated into seventeen microfacies types. Microfacies analysis and fauna contents have shown gradual facies variation grading from a high energy inner ramp environment in the east to a low energy deep water ramp environment in the west.